2006
DOI: 10.1016/j.yqres.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostratigraphic evidence from the Cold Creek bar for onset of ice-age cataclysmic floods in eastern Washington during the early pleistocene

Abstract: This study provides a detailed magnetostratigraphy of sediments composing the Cold Creek cataclysmic flood bar in the Pasco Basin, Washington. Our interpretation suggests onset of Missoula floods or similar events prior to 1.1 myr, later than previously suggested by Bjornstad et al. [Bjornstad, B.N., Fecht, K.R., Pluhar, C.J., 2001. Long history of pre-Wisconsin, Ice Age cataclysmic floods: evidence from southeastern Washington State. Journal of Geology 109 (6), 695–713]. Nonetheless these data suggest that Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Recent studies using the magnetic polarity of the Hanford formation sediments have shown that the earliest floods may have occurred as long ago as 2 million years. Four magnetic polarity reversals have been found in sediments from core holes in the 200 East Area (Pluhar et al 2006). These polarity reversals have paleosols at the top of each reversed sequence of sediments.…”
Section: 11mentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies using the magnetic polarity of the Hanford formation sediments have shown that the earliest floods may have occurred as long ago as 2 million years. Four magnetic polarity reversals have been found in sediments from core holes in the 200 East Area (Pluhar et al 2006). These polarity reversals have paleosols at the top of each reversed sequence of sediments.…”
Section: 11mentioning
confidence: 96%
“…Net erosion by these floods was minimal and probably associated with only the earliest floods; later floods only partially incised into older flood deposits before backfilling. Recent work on subdividing the Missoula flood deposits at the Hanford Site has shown that paleomagnetic polarity is a useful technique (Pluhar 2003;Pluhar et al 2006). In a detailed study at the 200 East Area, four magnetic polarity reversals were recognized (Figure 4.13).…”
Section: Hanford Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold Creek Bar grew as sediments were episodically laid down in series of perhaps hundreds of floods spanning a million years or more (Pluhar et al 2006). A network of braided flood channels sweeping across the bar locally scoured into the pre-existing deposits and backfilled with coarse sand and gravel.…”
Section: Hanford Formationmentioning
confidence: 99%
“…In general, the Hanford formation is subdivided into three principal facies associations: 1) graveldominated (GD), 2) sand-dominated (SD), and 3) interbedded sand-and silt-dominated (ISSD). The general distribution of these three facies associations is shown in Figure 2 (Pluhar et al 2006). A network of braided flood channels sweeping across the bar locally scoured into the preexisting deposits and backfilled with coarse sand and gravel.…”
Section: Hanford Formationmentioning
confidence: 99%